2005
DOI: 10.1111/j.1365-2036.2005.02492.x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell proliferation of the colonic mucosa in diverticular disease: a case–control study

Abstract: SUMMARYBackground: A higher risk of both advanced adenoma and carcinoma occurs in the sigmoid colon of patients with diverticular disease, for which bacterial carcinogens have been claimed to play a role. Aim: To assess epithelial cell proliferation in colonic mucosa of diverticular disease patients before and after rifaximin treatment. Methods: Twelve consecutive patients with a new endoscopic diagnosis of left-sided diverticular disease and 12 matched controls were enrolled. Epithelial cell proliferation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 41 publications
(108 reference statements)
0
19
0
Order By: Relevance
“…[96][97][98] As in IBD, 99 altering the intestinal micro-ecology can lead to a reduced influence on the immune response of the host and decreased bacterial production of short-chain fatty acids, which results from degradation of soluble fibre. 7,18,100,101 This may permit chronic inflammation and epithelial cell proliferation to develop in the colonic mucosa in and around the diverticula, 26,100,[102][103][104] as observed in acute diverticulitis ( Figure 1). 18,100 The degree of inflammation appears to be related to the severity of the disease.…”
Section: Evolution Of Medical Therapy Resulting From New Insights Intmentioning
confidence: 99%
“…[96][97][98] As in IBD, 99 altering the intestinal micro-ecology can lead to a reduced influence on the immune response of the host and decreased bacterial production of short-chain fatty acids, which results from degradation of soluble fibre. 7,18,100,101 This may permit chronic inflammation and epithelial cell proliferation to develop in the colonic mucosa in and around the diverticula, 26,100,[102][103][104] as observed in acute diverticulitis ( Figure 1). 18,100 The degree of inflammation appears to be related to the severity of the disease.…”
Section: Evolution Of Medical Therapy Resulting From New Insights Intmentioning
confidence: 99%
“…Chronic inflammation may be detected in the colonic mucosa harboring diverticula [11,12], and this chronic inflammation seems to be related to the severity of the disease [13]. A long-term history of chronic inflammation may lead to diverticulitis, first uncomplicated (confined to the bowel wall) and then complicated (with extension outside the bowel wall).…”
Section: Discussionmentioning
confidence: 97%
“…One of the possible explanations for the association between diverticular disease and colorectal cancer is that the presence of an inflammation process increases the risk for a malignant transformation [30] since, in the Western population, both diseases occur usually in the left colon. A study in patients with diverticular disease demonstrated that hyperproliferation of the colonic mucosa was localized in the upper third of the colonic crypts [31]. Hyperproliferation of the colonic mucosa was detectable in the whole length of the colonic crypts in the patients not only with symptomatic diverticulosis and acute diverticulitis but also in patients with asymptomatic diverticulosis [32].…”
Section: Discussionmentioning
confidence: 99%